'Restitutions of Body and Soil' in Mies Julie (2012): South African theatre audience receptions of Yaël Farber's adaptation of Strindberg's Miss Julie within a post-apartheid South African political landscape. Issue 1 (1st September 2016) - Keuris, Marisa
Abstract : Yaël Farber's2012 adaptation of August Strindberg's classic play Miss Julie entitled Mies Julie and subtitled Restitutions of Body and Soil since The Bantu Land Act No. 27 of 1913 and The Immorality Act No. 5 of 1927, received rave reviews internationally, earned a great number of awards, had sold-out performances and often received standing ovations from various international audiences. In this article I discuss why South African audiences' experience of Yaël Farber's South African adaptation of a classic play, Strindberg's Miss Julie, would differ to some extent from international audiences' reception of the play. The focus is on two aspects which would have impacted on local audiences and their reception of the play, namely the particular South African setting of the play, and its sociohistorical context. The three aspects foregrounded by the play's title: the aspect of 'indentured race-based servitude' as reflected in the title, Mies Julie; the Bantu Land Act, and thirdly, the Immorality Act, as reflected in the subtitle, are discussed in some detail to demonstrate why the political is more personal for local audiences than for international audiences.